Coordination of Timers and Sensors in Cell Signaling. (7th February 2019) - Qian, Junbin; Gelens, Lendert; Bollen, Mathieu
Abstract : Timers and sensors are common devices that make our daily life safer, more convenient, and more efficient. In a cellular context, they arguably play an even more crucial role as they ensure the survival of cells in the presence of various extrinsic and intrinsic stresses. Biological timers and sensors generate distinct signaling profiles, enabling them to produce different types of cellular responses. Recent data suggest that they can work together to guarantee correct timing and responsiveness. By exploring examples of cellular stress signaling from mitosis, DNA damage, and hypoxia, the authors discuss the common architecture of timer‐sensor integration, and how its added features contribute to the generation of desired signaling profiles when dealing with stresses of variable duration and strength. The authors propose timer‐sensor integration as a widespread mechanism with profound biological implications and therapeutic potential. Abstract : Biological timers and sensors generate distinct signaling profiles but work together to shape the desired cellular response to stresses of variable strength and duration. Here, the authors discuss the architecture of timer‐sensor integration and its widespread biological implications.